2017
DOI: 10.1007/s10461-017-1769-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanol (PEth) as a Biomarker of Alcohol Consumption in HIV-Infected Young Russian Women: Comparison to Self-Report Assessments of Alcohol Use

Abstract: Background Alcohol use is particularly deleterious for HIV-infected individuals and thus accurate assessment of alcohol consumption is crucial in this population. Phosphatidylethanol (PEth) provides an objective assessment of drinking and can be compared to self-reported alcohol assessments to detect underreporting. The purpose of this study was to identify underreporting and its potential predictors in an HIV-infected sample of young Russian women. Methods The current study examined the concordance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
4
25
0
3
Order By: Relevance
“…Self‐reported alcohol consumption can be biased (Devaux and Sassi, ; Stockwell et al., ). However, measurement of PEth as a biomarker of recent alcohol consumption correlated well with the self‐reported consumption estimates, and PEth is considered a valid measure to protect against consumption underestimation (Bajunirwe et al., ; Littlefield et al., ; Schröck et al., ; Stewart et al., ). Further assessments of the full cohort as the study progresses will add validity to these consumption estimates via repeat measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐reported alcohol consumption can be biased (Devaux and Sassi, ; Stockwell et al., ). However, measurement of PEth as a biomarker of recent alcohol consumption correlated well with the self‐reported consumption estimates, and PEth is considered a valid measure to protect against consumption underestimation (Bajunirwe et al., ; Littlefield et al., ; Schröck et al., ; Stewart et al., ). Further assessments of the full cohort as the study progresses will add validity to these consumption estimates via repeat measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Our results must be interpreted in light of study limitations, including the use of a cross-sectional design, which limits our ability to interpret the directionality of findings. Further, the rates of unhealthy alcohol use and underreporting may differ significantly by community and across distinct demographic groups; this is reflected in other work evaluating PEth in diverse samples, including HIV-infected young women in Russia [ 50 ], young people who inject drugs in the US [ 51 ], and veterans living with HIV and/or hepatitis C [ 52 ]. As such, these findings may not generalize to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, only about 50% of participants had a positive PEth biomarker at enrollment, which suggests that some women could have exaggerated their drinking behavior at baseline to enroll in a research study that paid cash incentives to participants. While PEth is clearly associated with drinking behavior in women at the aggregate level (Wang et al., ), some other studies have reported inconsistent results for PEth versus self‐reported drinking in women (Littlefield et al., ; Papas et al., ). It remains unclear how sensitive or specific a PEth result is for an individual woman, or how its test characteristics may vary according to the time between the last drinking episode and the PEth assessment (Moore et al., ).…”
Section: Discussionmentioning
confidence: 99%